New Insights Into Sunflower (Helianthus annuus L.) FatA and FatB Thioesterases, Their Regulation, Structure and Distribution - Aznar-Moreno, Jose A.; Sánchez, Rosario; Gidda, Satinder K.; Martínez-Force, Enrique; Moreno-Pérez, Antonio J.; Venegas Calerón, Mónica; Garcés, Rafael; Mullen, Robert T.; Salas, Joaquín J. (Frontiers in Plant Science, 2018)
Sunflower seeds (Helianthus annuus L.) accumulate large quantities of triacylglycerols (TAG) between 12 and 28 days after flowering (DAF). This is the period of maximal acyl-acyl carrier protein (acyl-ACP) thioesterase activity in vitro, the enzymes that terminate the process of de novo fatty acid synthesis by catalyzing the hydrolysis of the acyl-ACPs synthesized by the fatty acid synthase complex. Fatty acid thioesterases can be classified into two families with distinct substrate specificities, namely FatA and FatB. Here, some new aspects of these enzymes have been studied, assessing how both enzymes contribute to the acyl composition of sunflower oil, not least through the changes in their expression during the process of seed filling. Moreover, the binding pockets of these enzymes were modelled based on new data from plant thioesterases, revealing important differences in their volume and geometry. Finally, the subcellular location of the two enzymes was evaluated and while both possess a N-terminal plastid transit peptide, only in FatB contains a hydrophobic sequence that could potentially serve as a transmembrane domain. Indeed, using in vivo imaging and organelle fractionation, H. annuus thioesterases, HaFatA and HaFatB, appear to be differentially localized in the plastid stroma and membrane envelope, respectively. The divergent roles fulfilled by HaFatA and HaFatB in oil biosynthesis are discussed in the light of our data.